The Role of Social Capital in Improving the Welfare of Rice Farmers in Tangerang Banten Regency - Khaerul Saleh (Budapest International Research and Critics University, 2022)
This study tries to see how social capital plays a role in moving society so as to make people unite to achieve common goals based on unity, and is limited by the values and norms that grow and adhere to, as well as social relations inherent in social structures and social networks in a society. Community that makes it big. Various social obligations, create a climate of mutual trust, carry information channels, and establish social norms and sanctions for community members. In social capital, where trust is built from hope, honesty, and cooperative behavior that emerges from within a community based on the norms shared by members and is expected to be a solution in overcoming the consequences of the crisis. The population in this study consisted of rice farmers, community leaders, and government officials from 4 selected villages as samples. While the number of respondents was 98 people, consisting of 88 rice farmers, 4 community leaders, 4 village officials, and 2 officials. Research variables include studies of economics, socio-cultural, demographics, rice farmers, and the effectiveness of social capital. Collecting data using focus group discussions (FGD) with respondents, and field observations. The results show that the values of trust in social capital are dominant as the basis for rural communities to be used as a basis for improving other functions, such as increasing respect and mutual benefit. Problems in optimization problems concern the nature of social capital, human resource problems, and management problems. The main problem in optimizing the role of social capital in rural areas is the need for support from various stakeholders, and the demands of rural communities regarding the importance of mentoring programs to improve the competence of rural communities by improving farming skills, and increasing agricultural diversification. In addition, the need for transformational leadership support to increase the optimization of the role of social capital.